Latihan Bench Pull Terhadap Performa Sprint Kayak Pada Mahasiswa Universitas Tangerang Raya - Hidayat, M. Hariadi; Jubaedah, Siti; Annisa, Siti Nur; Hakim, Nurwahidin (Dharmas Journal of Sport, 2026)
This study aims to examine the effect of bench pull training on 200-meter kayak sprint performance in student-athletes at Universitas Tangerang Raya. A One-Group Pretest–Posttest Design was used with a sample of 10 student paddlers who completed a four-week training intervention. The research instrument consisted of a 200-meter sprint kayak time-trial conducted before and after the training program. Data were analyzed using a paired sample t-test. The results indicate a significant effect of bench pull training on sprint performance, as shown by a p-value of 0.005 (< 0.05) and a performance improvement of 9.9%, reflected in the reduction of mean time from 60.4 seconds to 54.4 seconds. These findings suggest that bench pull training enhances upper-body pulling strength, contributing to improved stroke efficiency and acceleration during kayak sprinting. Therefore, bench pull is recommended as a targeted strength-training modality for university athletes seeking to improve 200-meter kayak sprint performance.